Historical Construction of Local Food System Transformations in Lebanon: Implications for the Local Food System - Mukahhal, Walid; Abebe, Gumataw Kifle; Bahn, Rachel A.; Martiniello, Giuliano (Frontiers in Sustainable Food Systems, 2022)
Food system transformations occur in a complex political, economic, social, and territorial landscape. The study provides a historical construction of global food regime changes and the adaptiveness, transformability, and resilience of the local food system in Lebanon, a Middle Eastern context. Lebanon offers a unique opportunity to understand the influence of global food regimes and geopolitics on agriculture, the local food system, and capital accumulation. After the 1975–1990 Lebanese Civil War, Lebanon experienced food retail transformation and international penetration through foreign investments. These alterations have several implications for society and the local food system: farming households' influence on agricultural policies and the political commitment to support the farming community decreased. The paper concludes that Lebanon's local food system transformation is a manifestation of geopolitical events and global food regime changes. This may have important implications and pave the way for a new food system that is based on the revitalization of agriculture and new forms of geoeconomic partnerships with regional actors.